Adding value through new public leadership. Issue 4 (4th November 2014) - Reid, Linda
Abstract : Purpose: –The purpose of this paper is to report on doctoral research that is addressing how strategic partnerships are rethinking their approach to tackling domestic abuse in Manchester, UK, and creating a new Public Service Reform Commissioning Framework, involving a significant programme of collaboration across sectors, including local authorities, Greater Manchester Police, the Office of the Police and Crime Commissioner and voluntary not-for-profit agencies. Design/methodology/approach: – The methodological approach is a case study strategy (Yin, 1994). It is mainly qualitative, with multi-method data collection and analysis. The paper is a commentary on the research, rather than a research paper. Findings: – The paper explores the extent to which an innovative new public leadership approach (Brookes and Grint, 2010) to the strategy and governance framework has been adopted, and whether the partnership is succeeding in creating create public value (Moore, 1995). It will discuss how a more collaborative approach based on a community model can add greater engagement across the sectors. Originality/value: – Although there is a substantial body of literature about domestic abuse, there is an absence of research from a business and management perspective. The literature review identified that there is little about leadership approaches in tackling domestic abuse, or analysis of partnership approaches from a business and management perspective.